Four TRPM4 Cation Channel Mutations Found in Cardiac Conduction Diseases Lead to Altered Protein Stability - Bianchi, Beatrice; Ozhathil, Lijo Cherian; Medeiros-Domingo, Argelia; Gollob, Michael H.; Abriel, Hugues (Frontiers in Physiology, 2018)
Transient receptor potential melastatin member 4 (TRPM4), a nonselective cation channel, mediates cell membrane depolarization in immune response, insulin secretion, neurological disorders, and cancer. Pathological variants in TRPM4 gene have been linked to several cardiac phenotypes such as complete heart block (CHB), ventricular tachycardia, and Brugada syndrome (BrS). Despite recent findings regarding the functional implications of TRPM4 in cardiac diseases, the molecular and cellular mechanisms leading to altered conduction are poorly understood. In the present study, we identify and characterize four novel TRPM4 variants found in patients with CHB or ventricular fibrillation. Three of them, p.A101T, p.S1044C and a double variant p.A101T/P1204L, led to a decreased expression and function of the channel. On the contrary, the variant p.Q854R showed an increase in TRPM4 current. Recent evidence indicates that altered degradation rate of mutant proteins represents a pathogenic mechanism underlying genetic diseases. In consequence, protein turnover of WT-TRPM4 and TRPM4 variants overexpressed in HEK293 cells was analyzed using cycloheximide, an inhibitor of protein biosynthesis. Upon addition of cycloheximide, WT-TRPM4 decayed with a half-life of ̴ 20 hours, while loss-of-expression variants showed a ̴ 30% increase in degradation rate, with a half-life close to 12 hours. Together, the gain-of-expression variant showed a higher stability and a doubled half-life compared to WT-TRPM4. In conclusion, decreased or increased protein expression of several TRPM4 variants linked to cardiac conduction disorders or ventricular arrhythmias were found to be caused by altered TRPM4 half-life compared to the WT form.